The use of estrus synchronization and transcervical artificial insemination for out of season management of Najdi sheep in Saudi Arabia - AL-Sobayil, Khalid A., author; Johnson, LaRue, advisor; Kimberling, Cleon V., committee member; Mortimer, Robert G., committee member; Graham, James K., committee member (Colorado State University. Libraries, 2000)
The objective of this research was to evaluate the reproductive performance in both Rams and ewes of Najdi sheep during the time of the year when they exhibit low reproductive performance, April - September. In this study, the use of some reproductive management, such as: 1- Ram breeding soundness examination, 2- Estrus synchronization, 3- Transcervical AI and, 4- Pregnancy diagnosis by Real-time ultrasonic technique, were applied to Najdi sheep. A breeding soundness examination (BSE) involving physical as well as reproductive tract examinations, scrotal circumference (SC), and semen evaluation was done on 82 Najdi rams at the sheep unit that belong to National Agriculture Development Company (NADEC), located approximately six hundred km north-west of Riyadh, the capital city of Saudi Arabia. The farm is about 799 m above the sea level and the average maximum temperature during the hot months is approximately 40 ° C. Seventeen rams were classified as unsatisfactory breeders due to physical (10 rams) and reproductive (7 rams) problems. Semen evaluation showed that the majority of the tested Najdi rams had the ability to produce semen with adequate quality at the commencement of the hot months. The measurement of scrotal circumference showed that rams of this breed had smaller scrotal measurement (X= 31cm), as compared to North American breeds that have in average 34 cm. This could be due to the relatively small size of this breed and because the measurement took place at the time of low breeding performance. Twenty-two of the tested fertile rams were used for subsequent natural and artificial breeding. The use of estrus synchronization and transcervical AI were evaluated on 300 Najdi ewes that were assigned equally into three groups: 1) Group 1: control ; no hormonal treatment and ewes of this group were exposed to 8 BSE tested fertile Najdi rams for 17 days; 2) Group 2: treatment 1; ewes were synchronized with control intravaginal drug releasing devices (CIDRs) that contain 3g progesterone for 12 days and at the time of CIDRs removal, the ewes injected with 600iu PMSG and bred naturally by 10 tested fertile rams that were introduced for seven days; 3) Group 3: treatment 2; ewes were treated the same as treatment 1 one in regard to hormonal treatments, CIDRs and PMSG, but the ewes were transcervically inseminated 48-52 hours after CIDRs removal with 100x106 sperm as fresh extended semen. The results showed that the treated groups had a significant (α < .01) difference in regard to the number of ewes lambed and the number of lambs born per ewe. In addition, ewes in treatment 1 and 2 had shorter lambing period in comparison with the control group 9,10,21 days respectively. The ewes in the first and second treatment that had essentially known breeding dates were examined by real-time ultrasonic technique. An external 5MHz probe was used in this study. The ewes were tested at three different stages of pregnancy, 20, 40, and 60 days post breeding. The results showed a significant (α < 0.01) difference in the accuracy of pregnancy diagnosis in the three different diagnosing dates. The accuracy of pregnancy diagnosis was 66, 90, and 100% at 20,40, and 60 days post breeding. The economic aspect of using estrus synchronization, TCAI and real-time ultrasonography techniques were evaluated. The use of this reproductive technique decreased the cost of rams per ewe as well as the cost of ram per born lamb. This study started on April 22 and end on October 15, 1999.
Keywords: zoology; livestock; animal sciences